Delay-bandwidth and delay-loss limitations for cloaking of large objects - Johnson, Steven G. (2012)
We show that the difficulty of cloaking is fundamentally limited by delay-loss and delay-bandwidth limitations that worsen as the size of the object to be cloaked increases relative to the wavelength, using a simple model of ground-plane cloaking. These limitations must be considered when scaling experimental cloaking demonstrations up from wavelength-scale objects.